Synthesis, characterization and biological studies of oxovanadium (IV) complexes with 5-chloroisatin hydrazones (Funded Work) - HARIKESH KUMAR; SHIVANI; JITENDRA KUMAR PANDEY (International Journal of Pharma and Bio Sciences, 2019)
Oxovanadium (IV) complexes have been synthesized by reacting Oxovanadium (IV) sulphate with hydrazones derived from different aromatic (benzoic/4-chlorobenzoic/4-nitrobenzoic/4-methoxybenzoic/3-nitrobenzoic) acid hydrazides and 5-chloroisatin in ethanol in the presence of sodium acetate. All these complexes were characterized by elemental analyses, spectral techniques (UV-Vis, IR, and EPR) and magnetic moment measurements. The low molar conductance values indicate that they are non-electrolytes and the EPR spectra indicate that the free electron is in dxy orbital. A square pyramidal geometry is predicted for the synthesized complexes. In vitro antibacterial activity was determined by screening the compounds against Gram-negative (Escherichia coli) and Gram-positive Staphylococcus aureus and Bacillus subtilis) bacterial strains and in vitro antifungal activity was determined against fungi Aspergillus niger and Candida albicans. The oxovanadium (IV) complexes have a higher antimicrobial effect than free ligands.